2003
DOI: 10.1097/01.ccm.0000089945.69588.18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-acetylcysteine on nuclear factor-κB activation, interleukin-6, interleukin-8, and intercellular adhesion molecule-1 expression in patients with sepsis*

Abstract: Administration of N-acetylcysteine results in decreased nuclear factor-kappa B activation in patients with sepsis, associated with decreases in interleukin-8 but not interleukin-6 or soluble intercellular adhesion molecule-1. These pilot data suggest that antioxidant therapy with N-acetylcysteine may be useful in blunting the inflammatory response to sepsis. Further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 39 publications
8
105
0
6
Order By: Relevance
“…Thus, polymorphisms may exist in the Nrf2 gene that may identify subjects at risk for more severe sepsis. In a recent clinical trial, NAC was shown to reduce NF-κB activation as well as IL-8 secretion in patients with sepsis (19). However, in a subsequent randomized trial of 34 patients, NAC failed to improve end-organ function or microalbuminuria (20).…”
Section: Antioxidants and Sepsismentioning
confidence: 99%
“…Thus, polymorphisms may exist in the Nrf2 gene that may identify subjects at risk for more severe sepsis. In a recent clinical trial, NAC was shown to reduce NF-κB activation as well as IL-8 secretion in patients with sepsis (19). However, in a subsequent randomized trial of 34 patients, NAC failed to improve end-organ function or microalbuminuria (20).…”
Section: Antioxidants and Sepsismentioning
confidence: 99%
“…Neutrophils were immediately separated by single-step density gradient centrifugation, using Polymorphprep (AxisShield, Oslo, Norway) as previously described (16). The harvested cells were resuspended in RPMI 1640 culture medium supplemented with 10% heat-inactivated fetal calf serum, 20 mmol/liter L-glutamine, and 1% penicillin-streptomycin.…”
Section: Neutrophil Isolation Following Local Research Ethicsmentioning
confidence: 99%
“…With this decrease in inflammatory mediators, end-organ stimulation such as the liver to release acute phase proteins decreases, thereby decreasing the stimulation of endothelial dysfunction, ultimately preventing plaque formation and the occurrence of atherosclerosis. 20,23,24 Overall benefit of this study was 2 x 600 mg oral NAS for eight weeks to reduce IL-6 levels in CKD stage V patients undergoing CAPD, so that the incidence of atherosclerosis can be decreased.…”
Section: Discussionmentioning
confidence: 99%